The study of factors affecting behaviour digital marketing among University Malaysia Kelantan student’s - Mohamad Hakim Abdul Mukti; Ng Si Wei; Nor Izzati Johari; Nurul Hamizah Zaini (2024)
All throughout the world, digital marketing is becoming a regular part of daily life. In January 2021, 4.66 billion people, or 59.5% of the world's population, accessed the internet (Statista, 2021). As a result, business owners use a very proactive strategy to research the online consumer's behaviour, offer better goods and services, and maintain client relationships via digital channels. The problem from this study is, the findings of the previous study show that the attitude and intention to buy is not much influenced by the validity of the source of influence. Furthermore, the findings of this study show that influencers who endorse a product without having a deep understanding of the product directly oppose their followers' positive purchase intentions. The purpose of this study to examine the study of factors affecting behaviour digital marketing among University Malaysia Kelantan students. This study contained Performance expectancy, effort expectancy & facilitating conditions as the factor that affecting behaviour digital marketing. The method was used in this study is quantitative research study will be conducted online with 150 respondents among University Malaysia Kelantan students. For the findings, performance expectancy, effort expectancy and facilitating conditions have positive relationship with behaviour digital marketing. The data analysis was used are descriptive analysis, a reliability and validity test, and hypotheses testing followed by PLS-SEM algorithm and Bootstrapping. The Originality of the study, an experience study based on the behavior of Malaysia Kelantan University students in digital marketing. This paper is intended to see if the factors chosen by the researcher affect the behavior of Malaysia Kelantan University students related to digital marketing nowadays.